The Effect of Exposure to Escherichia coli with Low Molecular Weight Hyaluronan, High Molecular Weight Hyaluronan, Hyaluronidase in the Cervix Premature Pregnant Model of Balb/C Mice - Fikhy Rizky Hapsari; Suheni Ninik Hariyati; I Wayan Arsana Wiyasa; Teguh Wiyono; Dewi Santosaningsih (Asian Journal of Health Research, 2022)
Introduction: Infection is the biggest cause of preterm labor, about 25-40%, and ascending infection through the vagina is the most common route of infection. This study aims to evaluate the level of Low Molecular Weight Hyaluronan (LMWHA), level of High Molecular Weight Hyaluronan (HMWHA), and the level of the enzyme hyaluronidase in Balb/c premature labor due to infection with Escherichia coli model mice. Methods: This study used an actual experimental design carried out in the laboratory in vivo on balb/c mice exposure to Escherichia coli with a randomized post-test only with a control group design. In the premature model of exposure to Escherichia coli balb/c mice on the cervix of 109 CFU/ml, cervical samples were taken and the levels of LMWHA, HMWHA, and hyaluronidase were measured using spectrophotometry. This study was divided into 2 groups. Control group and treatment group. Results: Low Molecular Weight Hyaluronan (LMWHA) and of the hyaluronidase enzyme levels in premature Balb/C cervical mice exposed to E. coli were higher than in Balb/C cervical mice. High Molecular Weight Hyaluronan (HMWHA) levels in premature Balb/C cervical mice exposed to E. coli were lower Conclusion: In the cervix of the infected by E. coli mice model, LMWHA and hyaluronidase enzymes increased and HMWHA decreased.